(untitled) (Contemporary Journal of Social Science Review, 2025)
It is acclaimed that research papers by Pakistani writers are difficult to get published in the international journals (Bibi and Nawaz, 2022). Thus by modifying Hyland’s (2005) model of interaction, the current study attempts to investigate the prevalence of two stance markers, hedges and boosters, in academic writing across various portions of research articles. The researcher developed the corpus and it is based on collectively 196 research papers from the discipline of Arts and Humanities, particularly Linguistics. To conduct a comparative study and to map the interactional discourse in the academic writing of Pakistani and foreign writers, the corpus is divided into two major categories that is research papers by Pakistani writers and research papers by foreign writers. Antconc. (version 4.3.1) software was used to determine the frequencies of the chosen corpus. As a result, this paper conducts a comparative analysis to investigate how stance indicators are used by Pakistani writers and foreign writers. The findings of the study demonstrate that the authors of the Pakistani research papers use hedges abundantly as compared to non-Pakistani writers. Further, Pakistani researchers use boosters in quite less frequency as compared to non-Pakistani researchers. Thus, the research is important because it contributes to an investigation and understanding of how writers present their stance in research papers.